A Problem-based Learning Approach and Its Effects on the Writing Performance of Nigerian Undergraduates - Muhammad Mukhtar Aliyu; Yong Mei Fung; Sabariah Md. Rashid; Vahid Nimehchisalem (International Journal of Language Teaching and Education, 2020)
Writing is considered as an important but a difficult language skill for undergraduates. To develop writing skills, undergraduates need to be given the opportunity to interact with and help one another in the writing process. They also need to be supported by teachers in the process. However, most of the traditional teaching methods adopted by writing instructors in Nigeria do not allow students to interact in the learning process. In this light, this study investigates the effects of a problem-based learning approach (PBL) on the writing performance of Nigerian undergraduates. The study employed a pre- and- post-treatment quasi-experimental research design. The participants (n=18) involved in the study were an intact class of second-year students taking English composition course and two tutors in a college in North-eastern Nigeria. The study was conducted over a period of 12 weeks. To determine the effects of PBL on the participants’ writing performance, a rating scale was used to rate the content, organisation, vocabulary, grammar and mechanical accuracy of the pre- and post-treatment writing scripts. A paired-sample t-test analysis was run to compare the mean scores of the undergraduates’ pre- and post-treatment writing. The results showed significant improvements in all the components (content, organisation, vocabulary, language use and mechanics) of the participants’ writing in the post-treatment. The paper concludes with a discussion on the pedagogical and theoretical contributions of the findings. It provides writing instructors with a student-centred approach that would help to develop their students’ writing skills.